Analytical Study of the Impact of Islamic Values and the Role of Sufis Orders In West Africa - Garba, Mustapha; m, muhammed (Gezira Journal of Educational Sciences and Humanities; Vol 13 No 1 (2016), 2018)
This article surveyed “Analytical Study Of The Impact Of Islamic Values And The Role Of Sufi Orders In West Africa”; The methodology explored for this article was basically philosophical; this means the materials used came largely from published and unpublished sources. The primary focus is on how Islamic values increased West African economics, socio-political life, religious, intellectual activities, and cultural and syncretism among the various West African countries, the article also analyzed how Islam helped expand trading routes from just the Trans-Saharan to outside of Africa, like Europe, the Middle East, and Asia. Also Timbuktu and both the Mali and Songhai Empires becomes a major trading point. The 19 th century Jihads such as that of Sheikh Usman Dan Fodio brought about more far–reaching attempts to reform the whole socio-political, legal and economic system in line with the Qur’an and the practices of the Prophet (saw) and the righteous guided Caliphs. Sheikh Usman, a reformer, who was born in maratta Gobir in 1754 A.C. His father was a scholar and he personally taught sheikh Usman the Qur’an. Later sheikh Usman moved from place to place to be taught by other scholarly relatives. He was much impressed by one of his teachers in Agadesz, Jibril ibn Umar, through whom he was admitted in to a Sufi order. The impact of the Sufi orders in West Africa was spiritual, moral and occasionally political. As indicated, the orders offered a method of achieving spiritual advancement through training in mystical practices. At the same time the sense of belonging to a brotherhood and striving for moral purification under the guidance of a Sheikh would exert influence over the behavior of any Muslim who was seeking to please Allah. In this way the Sufi orders were themselves responsible for attracting people to Islam as well as providing an avenue of spiritual and moral advancement for born Muslims